Analisis Relevansi Bentuk, Makna, dan Fungsi Syair Adat dalam Upacara Segang sebagai Penguatan Pangan Lokal oleh Suku Soge di Maumere - Katharina Woli Namang; Gisela Nuwa; Elisabeth Henderika Dua Neang (Pusat Riset dan Inovasi Nasional, 2026)
This research is driven by the threat of losing the oral tradition of the Soge Tribe in Maumere, NTT, due to modernization, youth migration, and climate change disrupting local food security, with the Segang Ceremony serving as a vital ritual preserving agroecological wisdom. The aim is to analyze the relevance of the form, meaning, and function of Segang traditional chants to strengthen local food security amidst these challenges. The method employs qualitative ethnography through participatory observation and in-depth interviews with 12 informants, including tribal elders, farmers, and community members, conducted from August to September 2025, with data collected and processed thematically. Findings reveal the chants' form as three-part rhymed poetry with an adaptive bamboo flute rhythm, symbolic meaning of harmony between nature and ancestors supporting soil fertility and climate adaptation, and a function in passing down agroecological values through crop rotation and communal work, with a relevant example being the chant